2005
DOI: 10.1111/j.1540-8175.2005.03176.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Echocardiography Can Save Nondiagnostic Exams in Mechanically Ventilated Patients

Abstract: Patients in an intensive care unit (ICU) under mechanical ventilation (MV) are very difficult to image by transthoracic echocardiography, diminishing the beneficial information that could be obtained by this noninvasive approach. The objective of this study is to assess whether the addition of a contrast agent to fundamental imaging (FI) can improve or change the initial diagnosis in cardiac postoperative patients under mechanical ventilation by enhancing endocardial border delineation and Doppler flow signal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…One study showed an increase in the level of confidence of LVEF assessment from 56% to 91% after CE (10). Costa et al (11) showed a salvage rate of 77% of nondiagnostic studies. Furthermore, 16.7% of patients had a change of more than 10% in LVEF after contrast enhancement.…”
Section: Figure 5 Impact Of Contrast On Medication Changesmentioning
confidence: 98%
See 1 more Smart Citation
“…One study showed an increase in the level of confidence of LVEF assessment from 56% to 91% after CE (10). Costa et al (11) showed a salvage rate of 77% of nondiagnostic studies. Furthermore, 16.7% of patients had a change of more than 10% in LVEF after contrast enhancement.…”
Section: Figure 5 Impact Of Contrast On Medication Changesmentioning
confidence: 98%
“…Several studies have shown that CE improves the assessment of global and regional left ventricular (LV) function, enhances the detection of LV thrombi, and decreases variability of interpretation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). It has been estimated that 10% to 15% of routine echocardiograms have incomplete endocardial resolution, reaching 25% to 30% in critically ill patients in the intensive care unit (ICU) (14).…”
mentioning
confidence: 99%
“…Both American and European guidelines advocate the use of UCAs to improve endocardial border delineation when two or more segments of the left ventricle cannot be well defined [5, 6]. The salvage of such nondiagnostic studies using left ventricular opacification (LVO) has been reported to be as high as approximately 50% with higher rates of salvage in the intensive care unit [79]. It is only with the advent of contrast echocardiography that the percentage of nondiagnostic echocardiography studies has dropped to less than 5% [4].…”
Section: Clinical Utility Of Contrast Echocardiographymentioning
confidence: 99%
“…Reasons for this include the recumbency of the patient, positive pressure ventilation, suboptimal lighting conditions, inability to position the patient to optimize the imaging, and sternotomies/drains preventing acquisition of conventional echocardiographic views. The addition of contrast‐specific echocardiographic imaging can help overcome these limitations and improve ventricular structural and functional assessment in the critical care complex …”
mentioning
confidence: 99%